Adoption on new paddy seed varieties among farmers in Muda Agricultural Development Authority, Malaysia - Nazuri, Nur Shuhamin (2017)
Malaysia’s economic report stated that the rice production is expected to achieve 86% self-sufficiency level by 2010. Currently, Malaysia has reached self-sufficiency’s level for rice at 73% (9th Malaysia Plan). The contribution in an agricultural sector especially rice production is very important for generating self-sufficient rice, reducing imported rice and increasing food security. Agriculture sector is also important to provide income, increase the rate of employment and escalate investment especially in rural areas. Malaysian Agricultural Research and Development Institute (MARDI) is a research institute that is involves in supplying quality seeds and planting materials to the farmers. Meanwhile, government agency such as MADA provides support services for farmers’ development programs such as producing high quality of paddy seeds to enhance socio-economic of the farmers (Fauzi and Wahab, 2013). However, farmers encountered many problems due to lack of knowledge and practices on new paddy seed varieties. The yield performances are different according to areas and farmers although they are using the same seed variety. Farmers’ knowledge and skill are the main factors contributing to the yield performance.